Microorganism biodiversity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The biodiversity of microorganisms and invertebrates: its role in sustainable agriculture edited by D L Hawksworth 1991 302pp ISBN 0 85198 722 2 Hbk UKL40.00 CAB International, Wallingford Oxon OX10 ODE, UK